The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fnins.2019.00575
|View full text |Cite
|
Sign up to set email alerts
|

DMT1 Expression and Iron Levels at the Crossroads Between Aging and Neurodegeneration

Abstract: Iron homeostasis is an essential prerequisite for metabolic and neurological functions throughout the healthy human life, with a dynamic interplay between intracellular and systemic iron metabolism. The development of different neurodegenerative diseases is associated with alterations of the intracellular transport of iron and heavy metals, principally mediated by Divalent Metal Transporter 1 (DMT1), responsible for Non-Transferrin Bound Iron transport (NTBI). In addition, DMT1 regulation and its compartmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 118 publications
(169 reference statements)
0
30
0
Order By: Relevance
“…Iron metabolism is tightly regulated through a number of mechanisms and proteins. The upregulation of iron importer DMT-1 and downregulation of iron exporter ferroportin1 is a consequence of inflammatory stimuli and vice versa ( 26 , 27 ). Transferrin is able to buffer iron ( 28 ) but can also be rapidly effluxed from the brain to the blood ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Iron metabolism is tightly regulated through a number of mechanisms and proteins. The upregulation of iron importer DMT-1 and downregulation of iron exporter ferroportin1 is a consequence of inflammatory stimuli and vice versa ( 26 , 27 ). Transferrin is able to buffer iron ( 28 ) but can also be rapidly effluxed from the brain to the blood ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of DIO on DMT1 gene expression reported in the literature have focused primarily on male rodents and the system, leaving a knowledge gap on DIO impact in the brain and the effect of sex on potential gene expression alterations. More investigations are needed to learn about the gene expression of DMT1 in the brain under DIO conditions, as the dysregulation of DMT1 and trace element homeostasis is associated with various neurodegenerative diseases [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DMT1, another important iron-absorbing protein, is also closely associated with brain iron accumulation in neurodegenerative diseases. Multiple studies have shown that DMT1 overexpression contributed to iron accumulation in the substantia nigra and dopaminergic neuron loss (Salazar et al, 2008;Zhang et al, 2017;Ingrassia et al, 2019). Ferritin is the main intracellular iron storage protein composed of FTL1 (light chains) and FTH1 (ferritin heavy), which preserves excess iron in a redox inactive form and prevents the cell and tissue from oxidative damage (Theil, 2013;Dowdle et al, 2014;Lal, 2019).…”
Section: Ferroptosis and Ironmentioning
confidence: 99%